PENGARUH KERAGAMAN PRODUK DAN STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO BAROKAH TANI KECAMATAN MAJA KABUPATEN LEBAK - Ikbal Setiawan; Eris Harismasakti; Ade Jaya Sutisna (The Asia Pacific Journal Of Management Studies, 2024)
One of the problems faced by Barokah Tani Stores in Maja District is related to consumer decisions to buy their products. Many factors influence consumer decisions to buy products in a company, including product diversity and store atmosphere. Therefore, the purpose of this study was to determine: (1) the effect of product diversity on purchasing decisions at the Barokah Tani Shop, Maja District, Lebak Regency, (2) the effect of store atmosphere on purchasing decisions at the Barokah Tani Shop, Maja District, Lebak Regency, and ( 3) the effect of product diversity and store atmosphere on purchasing decisions at the Barokah Tani Shop, Maja District, Lebak Regency. This research was conducted using quantitative methods. The population of this study are all consumers who make purchases at the Barokah Tani Shop, Maja District. The research sample is part of a population of 79 consumers taken by accidental sampling technique. Data analysis using multiple regression analysis. The results of the research show that: (1) there is a positive and significant effect of product variety on purchasing decisions; (2) there is a positive and significant influence of store atmosphere on purchasing decisions; and (3) there is a significant influence of product variety and store atmosphere together on purchasing decisions.